2012
DOI: 10.1002/ijc.27811
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of vacuolar ATPase proton pumps inhibit human prostate cancer cell invasion and prostate‐specific antigen expression and secretion

Abstract: Vacuolar ATPases (V-ATPases) comprise specialized and ubiquitously distributed pumps that acidify intracellular compartments and energize membranes. To gain new insights into the roles of V-ATPases in prostate cancer (PCa) we studied the effects of inhibiting V-ATPase pumps in androgen-dependent (LNCaP) and androgen-independent (C4-2B) cells of a human PCa progression model. Treatment with nanomolar concentrations of the V-ATPase inhibitors bafilomycin A or concanamycin A reduced the in vitro invasion in both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
77
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(88 citation statements)
references
References 39 publications
10
77
1
Order By: Relevance
“…For Western blots, vacuolar protein (80 g) was separated by SDS-PAGE and transferred to nitrocellulose overnight at 150 mA. The V 1 A subunit was visualized with a 1:000 dilution of anti-human V 1 A rabbit polyclonal antibody (30); the antibody cross-reacts with the C. albicans protein.…”
Section: Methodsmentioning
confidence: 99%
“…For Western blots, vacuolar protein (80 g) was separated by SDS-PAGE and transferred to nitrocellulose overnight at 150 mA. The V 1 A subunit was visualized with a 1:000 dilution of anti-human V 1 A rabbit polyclonal antibody (30); the antibody cross-reacts with the C. albicans protein.…”
Section: Methodsmentioning
confidence: 99%
“…Increased cancer cell invasive activity is frequently associated with aberrant V‐ATPase plasma membrane localization suggesting that increased acidification of the extracellular space plays an important role 29, 33, 34, 37, 47, 48, 49, 50, 51, 52…”
Section: V‐atpase Function In Cancer Cellsmentioning
confidence: 99%
“…In prostate cancer cells, V‐ATPase co‐localized with prostate specific antigen (PSA; a secreted tumor marker that is regulated by the androgen receptor [AR]) in the Golgi and V‐ATPase inhibition resulted in a relocalization of PSA to lysosome‐like intracellular vesicles 50. Interestingly, in androgen‐sensitive LNCaP prostate cancer cells, V‐ATPase inhibition also reduced PSA mRNA expression, suggesting upstream inhibition of AR's transcription activating activity 50…”
Section: V‐atpase Function In Cancer Cellsmentioning
confidence: 99%
“…MCF10a cells are spontaneously immortalized breast epithelial cells derived from a patient with fibrocystic disease that are unable to form tumors in immunocompromised mice (28). MCF10CA1a cells are a highly invasive cell line derived from H-Ras-transformed MCF10a cells (MCF10AT) after selection for the ability to forms tumors in mice (29,32,34). The effect of treatment of MCF10a and MCF10CA1a cells with the specific V-ATPase inhibitor concanamycin (100 nM) on invasion was determined using an in vitro Matrigel invasion assay (33).…”
Section: The Effect Of V-atpase Inhibition On In Vitro Invasion Of MCmentioning
confidence: 99%
“…Importantly, administration of a V-ATPase inhibitor blocks bone metastasis of B16-F10 (28). A recent report has demonstrated that inhibition of V-ATPases blocks invasion of prostate cancer cell lines as well (29).…”
mentioning
confidence: 99%